2020
DOI: 10.3390/min10030227
|View full text |Cite
|
Sign up to set email alerts
|

5th-Century BC Himera and the Campanian Connection: Petrographic and Archaeological Studies on Western Greek Amphorae from Poseidonia and Elea Unearthed in the Necropolis of Himera

Abstract: Within the frame of an in-depth study of the corpus of about 560 western Greek transport amphorae (6th–5th century BC) yielded from excavations at the necropolis of the Dorian-Chalcidian colony of Himera in North-western Sicily, one of the most interesting issues consists in the determination of their provenance. Based on archaeological considerations, nearly 100 items have been attributed to southern Campania, specifically to Poseidonia and Elea. The present paper proposes a detailed combined archaeological-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…On the basis of both context dating and morphological comparisons, at present, the hypothetically local series represents the earliest amphora production of colonial Greek Sicily. The present joint study offers an archaeometric and archaeological characterization of western Greek amphorae manufactured in Himera (for a similar study on southern Campanian amphorae found in Himera, see [7]). It constitutes a benchmark for further research on the role of Sicily's westernmost Greek colony within the wider frame of the regional and supraregional commercial interaction between Greek, Punic and native communities in this border-region.…”
Section: Archaeological Background and Aimsmentioning
confidence: 83%
“…On the basis of both context dating and morphological comparisons, at present, the hypothetically local series represents the earliest amphora production of colonial Greek Sicily. The present joint study offers an archaeometric and archaeological characterization of western Greek amphorae manufactured in Himera (for a similar study on southern Campanian amphorae found in Himera, see [7]). It constitutes a benchmark for further research on the role of Sicily's westernmost Greek colony within the wider frame of the regional and supraregional commercial interaction between Greek, Punic and native communities in this border-region.…”
Section: Archaeological Background and Aimsmentioning
confidence: 83%